Assessing respiratory viral exclusion and affinity interactions through co-infection incidence in a pediatric population during the 2022 resurgence of influenza and RSV - Weidmann, Maxwell D.; Green, Daniel A.; Berry, Gregory J.; Wu, Fann (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction: In the Northeast US, respiratory viruses such as influenza and respiratory syncytial virus (RSV), which were largely suppressed by COVID-19-related social distancing, made an unprecedented resurgence during 2022, leading to a substantial rise in viral co-infections. However, the relative rates of co-infection with seasonal respiratory viruses over this period have not been assessed. Methods: Here we reviewed multiplex respiratory viral PCR data (BioFire Respiratory Pathogen Panel 2.1 [RPP]) from patients with respiratory symptoms presenting to our medical center in New York City to assess co-infection rates of respiratory viruses, which were baselined to total rates of infection for each virus. We examined trends in monthly RPP data from adults and children during November 2021 through December 2022 to capture the full seasonal dynamics of respiratory viruses across periods of low and high prevalence. Results: Of 50,022 RPPs performed for 34,610 patients, 44% were positive for at least one target, and 67% of these were from children. The overwhelming majority of co-infections (93%) were seen among children, for whom 21% of positive RPPs had two or more viruses detected, as compared to just 4% in adults. Relative to children for whom RPPs were ordered, children with co-infections were younger (3.0 vs 4.5 years) and more likely to be seen in the ED or outpatient settings than inpatient and ICU settings. In children, most viral co-infections were found at significantly reduced rates relative to that expected from the incidence of each virus, especially those involving SARS-CoV-2 and influenza. SARS-CoV-2 positive children had an 85%, 65% and 58% reduced rate of co-infection with influenza, RSV, and Rhino/enteroviruses, respectively, after compensating for the incidence of infection with each virus (p < 0.001). Discussion: Our results demonstrate that most respiratory viruses peaked in different months and present in co-infections less than would be expected based on overall rates of infection, suggesting a viral exclusionary effect between most seasonal respiratory viruses, including SARS-CoV-2, influenza and RSV. We also demonstrate the significant burden of respiratory viral co-infections among children. Further work is necessary to understand what predisposes certain patients for viral co-infection despite this exclusionary effect.